Fostering Student Politeness Through Religious Education Amid the Challenges of Social Media - Wardani, Vika Audina; Shodiq , Sadam Fajar (Universitas Muhammadiyah Sidoarjo, 2025)
Religious education plays an important role in shaping students' character and communication ethics, while social media can influence students' language patterns, both positively and negatively. Therefore, the purpose of this study is to analyze the extent to which religious education and the influence of social media play a role in improving students' language politeness in Islamic schools in Yogyakarta. Language politeness is an important issue in character education, especially amidst the challenges of social media development. This study uses a quantitative approach using a Likert scale survey processed with Smart-PLS. In this study, there were 230 students from two Islamic high schools in Yogyakarta who were the research samples. The results of the study indicate that both religious education and social media have a significant influence on students' language politeness. Social media shows a stronger influence than religious education, depending on how students use it wisely or otherwise. Theoretically, this study contributes to enriching the literature on character education and language pragmatics. These findings provide practical implications for teachers, parents, and schools to design a learning approach that integrates religious values ​​with digital literacy in order to form polite communication. Highlights: Dual Influence: Both religious education and social media significantly shape students' language politeness, with social media having a slightly stronger impact. Educational Integration: Findings highlight the need to blend religious values with digital literacy in school programs. Practical Relevance: Results inform teachers, parents, and schools to develop better communication ethics strategies amid social media challenges. Keywords: Religious Education, Language Politeness, Social Media, Character Education, Islamic Schools